REVIEW ON INDRAVARUNI (CITRULLUS COLOCYNTHIS SCHRAD): AN ETHNOMEDICINALLY RICH PLANT W.S.R. TO ITS THERAPEUTIC USES - Rohilla, *Lakhan; Singh, D.C; Yadav, Chhavi (International Journal of Ayurveda and Pharma Research, 2017)
Herbal medicines are being used by mankind for several years. In recent decade there has been a tremendous increase in interest towards plant based medicines, especially for new sources of drugs. Indravaruni is a well known plant of ancient medical sciences. It is described in almost all Samhitas and Nighantus of Ayurveda. Indravaruni is Citrullus colocynthis Schrad belongs to family Cucurbitaceae, mostly found throughout India, both wild and cultivated. Indravaruni is a trailing herb; its tendrils are simple, slender and hairy; leaves are variable in size with deltoid margin, pale green colour above and ashy colour beneath; It shows male and female flowers; fruit are globular slightly depressed green colour and get white glabrous when ripe. Fruit filled with dry spongy very bitter pulp. C. colocynthis is extensively used by the Ayurvedic practitioners to treat wide number disease. It is traditionally Practiced by various ethnic groups especially to treat Diabetes, Constipation, Abdominal Pain, Amennorhoea, Deafness, Rheumatism etc. Main chemical constituents of fruit pulp iscolocynthin, colocynthein and colocynthetin, pectin gum; seeds contain fixed oil and albuminoids. As per Ayurveda it is Tiktarasam, Usnaveeryam, Katuvipakam and used as purgative, diuretic Kaphaharam and abortifacient. This article review the taxonomical description, synonyms, vernacular names, classical review, part used, dosage, botanical description, Ayurvedic properties, phytochemistry, therapeutic uses, ethnomedicinal uses, pharmacological activity of Indravaruni.